Сравнительный анализ спектра мутаций гена фенилаланингидроксилазы в Новосибирской и Кемеровской областях - Батурина, О.А.; Тупикин, А.Е.; Бондарь, А.А.; Морозов, И.В. (Фактори експериментальної еволюції організмів, 2013)
Aims. The study summarizes the diversity of PKU-associated mutations of phenylalanine hydroxylase (PAH) gene in PKU patients from Kemerovo and Novosibirsk region. Methods. To reveal the PAH gene mutations, the researchers applied amplification of DNA fragments covering gene exons with subsequent sequencing of the amplification products. Results. The study has revealed both well-known mutations (R158Q, R252W, R261Q, P281L, IVS10–11G>A, R408W, IVS12+1G>A) and some rare (IVS2+5G>A, R155H, Y168H, W187R, E221_D222>Efs, A342T, Y386C, and IVS11+1G>C). Conclusions. We show here that mixed ethnic populations demonstrate a wider PKU allele diversity in comparison withCentral Russia.

Key words: phenylketonuria; PAH, mutation.